(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2020)
38 species and subspecies of Foraminifera, five of which are considered to be new, are recorded from Kazhdumi Formation of SW Iran. The recognized microfossil assemblages have proved being useful for biostratigraphic zonation, age determination and correlation of the examined rocks. Two zones and three subzones are proposed. Foraminiferal faunas indicate an Albian age for the Kazhdumi Fm. Lithologic and petrographical studies showed that the formation can be divided into three members.